@KPOPERS.HIJRAH: OTORITAS KEAGAMAAN DAN NEGOSIASI KESALEHAN DI KALANGAN K-POPERS MUSLIMAH MUDA INDONESIA: RELIGIOUS AUTHORITY AND NEGOTIATING PIETY AMONGST INDONESIAN FEMALE MUSLIM YOUTH K-POPERS - Iqomah Richtig; Rahmatullah (Jurnal Masyarakat dan Budaya, 2022)
Nowadays, the discourse of hijrah and dakwah has been popular on social media, particularly on Instagram. Instagram is one of primary platforms that disseminate these two discourses. There are a lot of dakwah accounts sprung up offering a variety of dakwah models based on their segmentations and focuses. One is @kpopers.hijrah. This account invites young Indonesian Muslim women addicted hallyu (Korean Wave) back to identity as pious Muslim. Through the posts, @kpopers.hijrah seeks to negotiate piety and religious devotion by involving hallyu elements and organizing several activities relevant to the purpose of hijrah. Through interview and netnography methods, the Authors argue that Instagram is not only a space for hijrah and da'wah for Muslim K-Popers but can also be used to suppress and inhibit the flow of the Korean wave. Given Instagram as the primary media which often used to practice hallyu consumerism.